2010
DOI: 10.1007/s00125-010-1899-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting insulin analogues elicit atypical signalling events mediated by the insulin receptor and insulin-like growth factor-I receptor

Abstract: Aims/hypothesis Insulin analogues were developed to improve the pharmacological properties of injected insulin and to better mimic endogenous insulin output. However, certain insulin analogues have been suggested to display IGF-I-like biological activities. Furthermore, several recent epidemiological studies have suggested a potential increase in cancer risk for treatment of diabetes patients with longacting analogue insulin glargine (A21Gly,B31Arg,B32Arg human insulin). Additional studies, however, reported n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…The strong activation of IGF1R by glargine is consistent with published studies showing that glargine exhibited a 6-8-fold increased affinity for IGF1R compared with insulin in CHO cells overexpressing the receptor (Kurtzhals et al, 2000). These results are also in agreement with previous reports from our laboratory (Weinstein et al, 2009;Yehezkel et al, 2010). In these studies we showed that glargine and detemir elicited atypical signaling activities and displayed enhanced IGF1-like proliferative and anti-apoptotic activities in colon, breast, and prostate cancer cell lines.…”
Section: Discussionsupporting
confidence: 95%
“…The strong activation of IGF1R by glargine is consistent with published studies showing that glargine exhibited a 6-8-fold increased affinity for IGF1R compared with insulin in CHO cells overexpressing the receptor (Kurtzhals et al, 2000). These results are also in agreement with previous reports from our laboratory (Weinstein et al, 2009;Yehezkel et al, 2010). In these studies we showed that glargine and detemir elicited atypical signaling activities and displayed enhanced IGF1-like proliferative and anti-apoptotic activities in colon, breast, and prostate cancer cell lines.…”
Section: Discussionsupporting
confidence: 95%
“…Some experimental studies have suggested that insulin stimulation of growth of cancers is mediated by insulin stimulation of IGF-I receptors [22]. While this possibility is not excluded by recent data, the documentation of expression of insulin receptors by malignant cells indicates that even insulins that have no IGF-I receptor agonist activity could stimulate proliferation [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some laboratory studies showed long-acting insulin analogs were associated with cancer cell proliferation and protected against apoptosis via their higher binding affinity to IGF-I receptors (3,4).…”
mentioning
confidence: 99%